(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
The present article presents and discusses two topics related to each other. The first topic refers to the dynamics and strategies in teaching or perfecting theatrical writing. That is, a contribution to a pedagogy of dramaturgy. The second topic is expressed through the presentation, followed by comments, of an excerpt of a text that aims to be theatrical. The text in concern, Hipólito, finds itself within the process of writing, and here we propose a partial reflection surrounding the writing process performed by us. Therefore, our article does not present final conclusions, remaining “open” until the writing process reaches an end, and by then we will be able to provide a better judgment of the text from its truthful place of enunciation, which is the theatrical space.